Evidence of Racial Bias Using Immersive Virtual Reality: Analysis of Head and Hand Motions During Shooting Decisions - Peck, Tabitha C.; Good, Jessica J.; Seitz, Katharina (IEEE transactions on visualization and computer graphics, 2021)
Shooter bias is the tendency to more quickly shoot at unarmed Black suspects compared to unarmed White suspects. The primary goal of this research was to investigate the efficacy of shooter bias simulation studies in a more realistic immersive virtual scenario instead of the traditional methodologies using desktop computers. In this paper we present results from a user study (N=99) investigating shooter and racial bias in an immersive virtual environment. Our results highlight how racial bias was observed differently in an immersive virtual environment compared to previous desktop-based simulation studies. Latency to shoot, the standard shooter bias measure, was not found to be significantly different between race or socioeconomic status in our more realistic scenarios where participants chose to raise a weapon and pull a trigger. However, more nuanced head and hand motion analysis was able to predict participants' racial shooting accuracy and implicit racism scores. Discussion of how these nuanced measures can be used for detecting behavior changes for body-swap illusions, and implications of this work related to racial justice and police brutality are discussed.